Analisis Kemampuan Menyelesaikan Soal Cerita Berdasarkan Literasi Matematika Materi Trigonometri Pada Kelas XI SMAN 1 Lembar - Hafifa, Winda; Arjudin, Arjudin; Salsabila, Nilza Humaira (Griya Journal of Mathematics Education and Application, 2025)
This study aims to describe the ability of grade XI students at SMA Negeri 1 Lembar in solving trigonometry story problems based on their level of mathematical literacy. This study employs a qualitative descriptive approach with six eleventh-grade students from class XI-1 as subjects, two each from the high, moderate, and low literacy categories. Data were collected through story problem tests and interviews, then analyzed using the Miles and Huberman model: data reduction, data presentation, and conclusion drawing. This study used a mathematical literacy framework that included formulate (formulating situations mathematically), employ (applying mathematical concepts, facts, procedures, and reasoning), and interpret (interpreting, applying, and evaluating mathematical results). The results of the study show that high-level students are able to perform all three processes well: understanding the context of the problem (formulate), applying formulas and procedures correctly (employ), and interpreting results and drawing conclusions according to the context (interpret). Meanwhile, intermediate-level students are sufficiently capable of identifying information and formulating problems (formulate), applying formulas although not yet systematically (employ), and drawing logical conclusions although there are still errors (interpret). Meanwhile, low-level students have difficulty formulating problems (formulate), use formulas in a limited and inaccurate manner (employ), and are unable to interpret results and draw conclusions correctly (interpret), although they are beginning to show basic understanding.